Hubungan Karakteristik Perjalanan Dan Sosial Ekonomi Mahasiswa Terhadap Perilaku Perjalanan Pengguna Sepeda Motor Untuk Tujuan Belajar dan Belanja - Chindy Trianingsih Siagian; Retno Widjajanti (Jurusan Perencanaan Wilayah dan Kota, 2020)
Students travel from one place to another because their needs cannot be met where he lives. Student travel patterns produce travel behavior. Travel behavior can be influenced by socio-economic aspects of the economy and travel characteristics. Gender, age, monthly allowance, daily expenses, parking fees, distance of residence to shopping places influence on student travel behavior. As many as 28% of students using motorcyles have a frequency of traveling as much as 7 times in one day. On the other hand, age also affects the travel time of students. The most travel patterns undertaken by students are dwellings / boarding houses - other places - shopping places - dwellings / boarding houses. Women tend to have a longer duration of activity compared to men, in addition students who have activity durations more than 7 hours and the frequency of travel is less than 5 times suspected to be a native of Semarang students so that they fulfill their activities in one place. In addition to saving on transportation costs, it will also save travel time for the student.